Development and validation of the intention to use the ICD-11 questionnaire in the Malaysian medical records context. - Erwyn Chin Wei Ooi; Zaleha Md Isa; Mohd Rizal Abdul Manaf; Ahmad Soufi Ahmad Fuad; Azman Ahmad; Mimi Nurakmal Mustapa; Nuraidah Mohd Marzuki; Cik Noor Baayah Abdul Jalil; Catherina William Totu (PLoS ONE, 2024)
As health systems transition to ICD-11, it is essential to gauge the readiness and improve existing transition efforts. Assessing the intention to use ICD-11 and factors influencing it is imperative to encourage the use of ICD-11 among the medical record officers (MROs) and assistant medical record officers (AMROs). This study aims to develop and validate a questionnaire on the factors influencing the intention to use ICD-11 among MROs and AMROs in the Ministry of Health, Malaysia. This study comprised a questionnaire development and validation involving 292 participants nationwide from Ministry of Health Malaysia facilities. The questionnaire was developed based on items adapted from the literature. Forward and backward English-Malay translation was done. Then, the questionnaire was examined for content validity, internal consistency reliability, construct validity, face validity, convergent validity, discriminant validity and confirmatory factor analyses. The final version of the questionnaire consists of eleven domains represented by 50 items. The content validity index and modified kappa were excellent for all domains. The Kaiser-Meyer-Olkin sampling adequacy value was appropriate, with a value of 0.790. The questionnaire also demonstrated good internal consistency reliability with Cronbach's alpha values between 0.850 and 0.992. Confirmatory factor analysis showed a reasonable fit for this eleven-factor model. In conclusion, this questionnaire provides a reliable tool for investigating the intention to use ICD-11 among MROs and AMROs. Positive findings from the psychometric properties support the validity of the questionnaire. This instrument can potentially support personnel in charge of ICD codification, guide the ICD-11 transition at various levels and facilitate research on support dynamics among the MROs and AMROs.